1983
DOI: 10.1002/jat.2550030304
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effects of aqueous extracts of Symphytum officinale L. and of its alkaloidal fractions

Abstract: Symphytum officinale L. (Boraginaceae) is a medicinal plant widely used in therapy. It roots, described in the Polish Pharmacopoeia as Radix symphyti, are recommended as expectorants, especially for children. Aqueous solutions of three alkaloid fractions obtained from infusions of Symphytum officinale L. root were tested for their antimitotic and mutagenic activity in meristematic cells of the lateral roots of Vicia faba L., var minor. Lasiocarpine, a proven carcinogen, served as a positive control. Mutagenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…Using the Ames test strains Salmonella typhimurium TA98 and TA100, comfrey extracts (mainly PA) did not produce a positive genotoxic response in the presence and absence of S9, although adverse effects were found with TA98 (White et al, 1983). Using a plant test, Furmanowa et al (1983) examined the mutagenic effects induced by comfrey extracts as well as lasiocarpine, which is a known carcinogen and served as a positive control in the study. Results showed that aqueous extracts of comfrey roots exerted antimitotic effects and induced chromosomal aberrations (CA).…”
Section: Genotoxicity Of Comfreymentioning
confidence: 99%
“…Using the Ames test strains Salmonella typhimurium TA98 and TA100, comfrey extracts (mainly PA) did not produce a positive genotoxic response in the presence and absence of S9, although adverse effects were found with TA98 (White et al, 1983). Using a plant test, Furmanowa et al (1983) examined the mutagenic effects induced by comfrey extracts as well as lasiocarpine, which is a known carcinogen and served as a positive control in the study. Results showed that aqueous extracts of comfrey roots exerted antimitotic effects and induced chromosomal aberrations (CA).…”
Section: Genotoxicity Of Comfreymentioning
confidence: 99%
“…Orta Çağ'da karakafes otunun kullanım alanlarına romatizma ve gut tedavisi eklenmiş, 1616-1654 yıllarında "The English Physician" adlı eserde karakafesotunun birleştirici etkisinden de bahsedilmiştir [21]. 20. yüzyılda karakafesotu periosteum problemlerinde, kemik kırıklarında, kallus oluşumunun desteklenmesinde, kırık sonrası nevraljide, kemik mineralizasyonunun hızlandırılmasında [21][22][23], kontüzyonlarda, tenosinovit ve kas iltihabında, hematomda, trombozda, artritte, kötü iyileşen yaralarda, cilt lekelerinde, flebit, periodontozda, gastrit, peptik ülser, öksürük, balgam söktürücü, romatizma, plörezi, bronşit, ishal ve tümör gibi rahatsızlıklarda kullanılmıştır [24][25][26][27][28][29][30]. Tıbbi kullanımının yanı sıra yemeklerde kullanılmış ve çiftlik hayvanlarını beslemek için yem olarak yetiştirilmiş, 1840'lı yıllarda İrlanda'daki patates kıtlığı sırasında gıda olarak da kullanılmıştır [21].…”
Section: Geçmişte Ve Günümüzde Karakafesotu'nun Geleneksel Kullanımıunclassified
“…In einigen Mutagenitätstests wurden Gemische von extrahierten PAs für die Bestimmung der mutagenen Wirksamkeit eingesetzt, wobei Interaktionen zwischen den individuellen PAs mit abschwächender oder auch fördernder Wirkung auftreten können. In einer Pflanzenextraktstudie mit Symphytum-officinale-PA-Gemischen wurde ein eindeutig mutagener Effekt dokumentiert (24). Ebenso verursachten Beinwellextrakte sowohl SCEs an menschlichen Lymphozytenkulturen als auch Chromosomenaberrationen (3).…”
Section: Genotoxizität Und Kanzerogenität Der Pyrrolizidinalkaloideunclassified